2012
DOI: 10.1186/1477-7827-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome in donor oocyte pregnancies: a matched-pair analysis

Abstract: BackgroundTo investigate the obstetrical and perinatal impact of oocyte donation, a cohort of women who conceived after OD was compared with a matched control group of women who became pregnant through in vitro fertilisation with autologous oocytes (AO).MethodsA matched-pair analysis has been performed at the Centre for Reproductive Medicine of the UZ Brussel, Dutch speaking Free University of Brussel. A total of 410 pregnancies resulted in birth beyond 20 weeks of gestation occurring over a period of 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 37 publications
5
58
2
5
Order By: Relevance
“…However, it has become clear that OD pregnancy is associated with an increased risk of gestational hypertension, preeclampsia, preterm birth, low birth weight, bleeding complications, and miscarriage compared with natural pregnancy or IVF pregnancy [1,7,16,24,28,29,35,38,49,59,64,68,69,78,80].…”
Section: Introductionmentioning
confidence: 98%
“…However, it has become clear that OD pregnancy is associated with an increased risk of gestational hypertension, preeclampsia, preterm birth, low birth weight, bleeding complications, and miscarriage compared with natural pregnancy or IVF pregnancy [1,7,16,24,28,29,35,38,49,59,64,68,69,78,80].…”
Section: Introductionmentioning
confidence: 98%
“…However, pregnancies achieved with donated oocytes are associated with a high incidence of first trimester bleeding and a 2-to 3-fold higher risk of gestational hypertension and pre-eclampsia when compared with conventional IVF (Serhal and Craft, 1989;Abdalla et al, 1998;Sö derstrom-Anttila et al, 1998;Yaron et al, 1998;Klein and Sauer, 2002;Sheffer-Mimouni et al, 2002;Wiggins and Main 2005;van der Hoorn et al, 2010;Stoop et al, 2012). The incidences of intrauterine growth restriction, preterm birth (PTB) and birth defects have mostly been comparable with conventional IVF (van der Hoorn et al, 2010), although impaired fetal growth in OD pregnancies when compared with conventional IVF has been noted (Gibbons et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We performed subgroup analysis for four studies with twin pregnancies, and the fixed‐effect model showed that hypertensive disorders of pregnancy were significantly higher in DO twin pregnancy than in the autologous twin pregnancy group [ n / N = 89/229 (38%) versus n / N = 948/5630 (16%), OR 3.69, 95% CI 2.62–5.19, I 2 = 0%; Figure ]. The subgroup analysis for PET in singleton DO pregnancies included four studies, and the fixed‐effect model showed that the risk of PET was significantly higher in singleton DO pregnancy [ n / N = 66/606 (10%) versus n / N = 333/10193 (3%), OR 2.90, 95% CI 1.98–4.24, I 2 = 0%; Figure ]. The fixed‐effect model meta‐analysis of five studies showed that the risk of PIH in singleton DO pregnancy is significantly higher when compared with singleton IVF pregnancy [ n / N = 99/577 (17%) versus n / N = 522/10211 (5%), OR 3.08, 95% CI 2.26–4.19, I 2 = 0%; Figure ] .…”
Section: Resultsmentioning
confidence: 99%
“…The subgroup analysis for PET in singleton DO pregnancies included four studies, and the fixed‐effect model showed that the risk of PET was significantly higher in singleton DO pregnancy [ n / N = 66/606 (10%) versus n / N = 333/10193 (3%), OR 2.90, 95% CI 1.98–4.24, I 2 = 0%; Figure ]. The fixed‐effect model meta‐analysis of five studies showed that the risk of PIH in singleton DO pregnancy is significantly higher when compared with singleton IVF pregnancy [ n / N = 99/577 (17%) versus n / N = 522/10211 (5%), OR 3.08, 95% CI 2.26–4.19, I 2 = 0%; Figure ] . Additionally, the subgroup analysis fixed‐effect model of two studies of women older than 40 years of age showed that the risk for hypertensive disorders was still significantly higher with DO pregnancy compared with IVF pregnancy [ n / N = 30/129 (23%) versus n / N = 18/168 (10%), OR 2.33, 95% CI 1.21–4.49, I 2 = 2%; Figure ] .…”
Section: Resultsmentioning
confidence: 99%